2014
DOI: 10.1016/j.jsps.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on Adverse Drug Reactions of antibiotics in a tertiary care hospital

Abstract: Adverse reactions are the recognized hazards of drug therapy and they can occur with any class of drugs and many studies revealed that the incidence is more in case of antibiotics. The main aim of this study was to detect and analyze Adverse Drug Reactions of antibiotics in inpatients of a tertiary care hospital. A prospective spontaneous reporting study by active and passive methods was carried out for a period of six months. A total of 49 ADRs were reported during the study period with male predominance (53.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
85
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(136 citation statements)
references
References 14 publications
22
85
7
1
Order By: Relevance
“…These data correlate with the study of Starveva et al, Jimmy Jose et al, Priyadharshini et al, where the causality was possible in most of the ADRs. 7,12,16,17 Preventability was assessed by Shumock and Thornton method which showed that majority of the reactions were not preventable 130 (57%) and only 24 (11%) were preventable which also shows that rational antibiotic policy plays an important role in selection of the antibiotics which exists in our hospital. According to a study conducted by Bates, antibiotics were responsible for 9% of preventable and 30% of nonpreventable ADRs.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…These data correlate with the study of Starveva et al, Jimmy Jose et al, Priyadharshini et al, where the causality was possible in most of the ADRs. 7,12,16,17 Preventability was assessed by Shumock and Thornton method which showed that majority of the reactions were not preventable 130 (57%) and only 24 (11%) were preventable which also shows that rational antibiotic policy plays an important role in selection of the antibiotics which exists in our hospital. According to a study conducted by Bates, antibiotics were responsible for 9% of preventable and 30% of nonpreventable ADRs.…”
Section: Discussionmentioning
confidence: 87%
“…8,12,13 Males were slightly more affected than females by the ADRs due to antibiotics in our study. Predominance of any gender being affected by ADR may also be due to the number of males or females admitted to the hospital during that period as seen in the study conducted by Shamna et al 7 Geriatric patients were more prone to antibiotic ADRs due to age related pharmacokinetic and pharmacodynamic changes and the presence of co-morbid illnesses and polypharmacy along with infectious diseases. In our study, age-wise distribution showed the predominance of adult patients followed by geriatric and pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations